TOWARDS RECONCILIATION AS A RESPONSE TO RELIGIOUS AND SOCIAL CONFLICTS IN AN INDONESIAN CONTEXT - Hatmoko, Tomas Lastari (Bahasa Indonesia, 2023)
Religious and social conflict is a problem that often occurs in the world. This problem has caused many victims, both the dead and those who were traumatized. Indonesia is a country that experiences inter-religious and social conflicts as well. A number of bloody events have occurred in several places. The focus of this paper is responding to these events especially in a Christian context. This is a concern because a number of conflicts and victims also involve Christians. In the midst of Christian life with other religions and social diversity, efforts to build reconciliation and peace are the main targets to be discussed in this paper. The author uses the literature method in this article. Through various literature, the author explores the idea of ​​reconciliation and offers several solutions, especially those that can be realized in the Indonesian context. This study invites anyone, especially members of the Church, to be involved in reconciliation in order to build peace in living together.